No Place like Home: Place-Based Attachments and Regional Science - John V. Winters (Institute of Labor Economics (IZA), 2022)
Place-based attachments are important but often overlooked. Place-based attachments can be beneficial but often harm individuals tied to struggling areas. In this address, I discuss my own education and migration experiences and then more generally discuss sense of belonging as a friction to migration. I also present descriptive statistics related to place-based attachments. Most persons born in the U.S. live in their birth state as adults. Birth-state residence has increased over time, especially among the highly educated. I also present evidence that college graduates who reside in their birth state experience a wage penalty that is increasing over time.
Keywords: R10; R23; J61; 330; location; place; regions; migration frictions; policy